Anxiety and Salivary Cortisol Levels in Children Undergoing Esophago-Gastro-Duodenoscopy Under Sedation - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2019)
Objectives: Esophagogastroduodenoscopy (EGD) can cause fear and anxiety in children. Cortisol, which is the most important glucocorticoid hormone in humans, can increase under physiological stress. The purpose of this study was to measure the salivary cortisol level (SCL) and anxiety level in patients undergoing EGD and evaluate their effects on the procedure. Methods: Children undergoing EGD under sedoanalgesia with propofol for various reasons were included. Their basal SCLs were compared with those of healthy age- and sex-matched controls. Moreover, SCL of the patient group at 30 minutes before EGD and 2 hours after the procedure were measured. Their anxiety scores were calculated using the modified Yale Preoperative Anxiety Scale before EGD. Duration of endoscopy, sedation, and recovery and total propofol doses were recorded. Results: Demographic properties of the patient group (n = 119; 10.9 +/- 3.2 years; 43.7% boys) and control group (n = 85; 11.8 +/- 2.8 years; 45.1% boys) were not significantly different. Basal SCLs of both groups were similar (16.9 +/- 0.7 vs 19.7 +/- 1.8 ng/mL, P = 0.16). SCL before EGD in the patient group was significantly higher than basal and post-EGD values (P < 0.001 for each). Pre-EGD SCL was positively correlated with anxiety level, propofol dose, and duration of sedation, procedure, and recovery. Anxiety levels of patients were positively correlated with propofol dose and duration of sedation and recovery, and negatively correlated with age. Conclusions: Childhood EGD is a significant stress factor, which was reflected by the pre-procedural SCL in this study. Increased anxiety resulted in increased propofol doses and sedoanalgesia-related procedural durations, which may cause potential complications.
Keywords: anxiety; propofol; salivary cortisol; sedoanalgesia; PROCEDURAL SEDATION; PROPOFOL; DISTRESS; STRESS